Ribociclib, a CDK 4/6 inhibitor, plus endocrine therapy in Asian women with advanced breast cancer. Issue 9 (28th July 2020) - Yap, Yoon‐Sim; Chiu, Joanne; Ito, Yoshinori; Ishikawa, Takashi; Aruga, Tomoyuki; Kim, Seung Jin; Toyama, Tatsuya; Saeki, Toshiaki; Saito, Mitsue; Gounaris, Ioannis; Su, Fei; Ji, Yan; et al.
Abstract: The ongoing, Phase Ib MONALEESASIA study is evaluating the efficacy and safety of ribociclib plus endocrine therapy in Asian patients with hormone receptor‐positive, human epidermal growth factor receptor 2‐negative advanced breast cancer. Eligible patients from Japan, Hong Kong, and Singapore were enrolled in this 2‐phase study consisting of a dose‐escalation phase to determine the maximum‐tolerated dose and the recommended Phase II dose of ribociclib plus letrozole, and a dose‐expansion phase to evaluate safety and tolerability of ribociclib plus letrozole, fulvestrant, or tamoxifen. An exploratory biomarker analysis evaluating expression of target genes was also conducted. In the dose‐escalation phase, the maximum‐tolerated/recommended Phase II doses of ribociclib were lower in Japanese patients (300 mg) than in Asian non‐Japanese patients (600 mg). Ribociclib plus endocrine therapy at the recommended Phase II dose had a manageable safety profile, with neutropenia and elevated liver transaminases being the most common adverse events leading to dose modifications or discontinuations, and it demonstrated evidence of clinical activity in both Japanese and Asian non‐Japanese patients. Preliminary efficacy in Asian populations is similar to that observed in White populations studied in previous ribociclib (MONALEESA) trials. Biomarker analysis demonstrated suppression of pharmacodynamic biomarker gene expression, indicating inhibition of target genes by ribociclib combined with endocrine therapy. Results from the ongoing study support the use of ribociclib in combination with letrozole in Asian non‐Japanese patients at the same dose (600 mg) as White patients. In Japanese patients, a lower dose of ribociclib (300 mg) should be considered. Clinicaltrials.gov: NCT02333370. Abstract : The recommended Phase II dose of ribociclib, a CDK4/6 inhibitor, when given with endocrine therapy, was determined in Asian patients with HR+, HER2– advanced breast cancer. The recommended dose was established to be lower in Japanese patients, but similar in Asian non‐Japanese patients, compared with White patients. Importantly, the combination therapies presented a manageable safety profile and demonstrated evidence of clinical activity in both Asian populations, supporting the use of ribociclib in the treatment of these patients.